2004
DOI: 10.1111/j.1365-2796.2004.01405.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of classical risk factors to cardiovascular disease in familial hypercholesterolaemia: data in 2400 patients

Abstract: Objective. To determine the contribution of classical risk factors to the development of cardiovascular disease (CVD) in patients with heterozygous familial hypercholesterolaemia (FH). Design. A retrospective, multi-centre, cohort study. Extensive data were collected by scrutinizing medical records and the use of questionnaires. Multivariate Cox regression was used to study the relationship between potential risk factors and the occurrence of CVD. Setting and subjects. We included 2400 FH patients from 27 Dutc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
155
1
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(182 citation statements)
references
References 30 publications
15
155
1
11
Order By: Relevance
“…5 Previously, we performed a retrospective multicentre cohort study of 2400 FH patients, of whom 782 patients (32.6%) had at least one cardiovascular event during an average follow up of 66 years. 6 In this cohort, we demonstrated that LDL-C levels are more important than the LDLR mutation type in determining the age of onset of CAD. 7 We also showed that classical risk factors including male gender, smoking, hypertension, type 2 diabetes, low levels of high-density lipoprotein cholesterol (HDL-C) and elevated lipoprotein(a) levels were independent risk factors for the development of CAD.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…5 Previously, we performed a retrospective multicentre cohort study of 2400 FH patients, of whom 782 patients (32.6%) had at least one cardiovascular event during an average follow up of 66 years. 6 In this cohort, we demonstrated that LDL-C levels are more important than the LDLR mutation type in determining the age of onset of CAD. 7 We also showed that classical risk factors including male gender, smoking, hypertension, type 2 diabetes, low levels of high-density lipoprotein cholesterol (HDL-C) and elevated lipoprotein(a) levels were independent risk factors for the development of CAD.…”
Section: Introductionmentioning
confidence: 59%
“…As previously reported, established risk factors do associate with the risk of CAD in FH patients. 8,22 However, none of the tested CAD-associated SNPs significantly modified the risk of CAD in our FH cohort in analyses unadjusted or adjusted for established cardiovascular risk factors. The lowest observed P-value of association was for a SNP in the SMARCA44 gene, near the LDLR gene (in adjusted analysis; P ¼ 0.021 ); however, it showed a paradoxically protective effect.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…13 Cross-tabulation and stepwise forward regression analysis of genome-wide significant polymorphisms in the LDLR gene region were performed using SPSS version 15 To replicate our results, we compared the genotype frequencies of the ten most significant polymorphisms between a second cohort of 2189 patients with clinical FH and another population-based control sample consisting of 2157 subjects of the Rotterdam study (RS-II). 12,14 The above-described Illumina chips were used to genotype the subjects of the RS-II. In the second FH cohort, the polymorphisms were genotyped using TaqMan (Applied Biosystems, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%